Validation of an ear-worn sensor for gait monitoring using a force-plate instrumented treadmill - Atallah, L.; Wiik, A.; Jones, G. G.; Lo, B.; Cobb, J. P.; Amis, A.; Yang, G. Z. (Gait and Posture, 2012)
A force-plate instrumented treadmill (Hp Cosmos Gaitway) was used to validate the use of a miniaturised lightweight ear-worn sensor (7.4 g) for gait monitoring. Thirty-four healthy subjects were asked to progress up to their maximum walking speed on the treadmill (starting at 5 km/h, with 0.5 km increments). The sensor houses a 3D accelerometer which measures medio-lateral (ML), vertical (VT) and anterior-posterior (AP) acceleration. Maximum signal ranges and zero crossings were derived from accelerometer signals per axis, having corrected for head motion and signal noise. The maximal force, measured by the instrumented treadmill correlated best with a combination of VT and AP acceleration (R-squared = 0.36, p = 0), and combined VT, ML, and AP acceleration (R-squared = 0.36, p = 0). Weight-acceptance peak force and impulse values also correlated well with VT and AP acceleration (Weight acceptance: R-squared = 0.35, p = 0, Impulse: 0.26, p = 0), and combined VT, ML, and AP acceleration (Weight acceptance: R-squared = 0.35, p = 0, Impulse: 0.26, p = 0). Zero crossing features on the ML axis provided an accurate prediction of the gait-cycle, with a mean difference of 0.03 s (-0.01, 0.05 confidence intervals).